The Principal's Role as Manager and Teacher Pedagogical Competence in Online Learning - Ngaziah, Nur; Pratiwi, Umi; Fatmaryanti, Siska Desy; Fakhrina, Aulia; Linda, Rizky Fadjar Choirrul (Universitas Pendidikan Ganesha, 2021)
The Covid-19 pandemic requires people to study online, one of which is at the elementary school level. Principals and teachers are the most important elements in the process of teaching activities, so they are required to quickly adapt to changes in the learning system. Principals must be able to play a role as managers in managing learning during the Covid-19 Pandemic. Likewise, teachers are required to maintain their pedagogical competence during online learning. This study aims to analyze the role of the principal as a manager and the pedagogical competence of teachers in online learning during the Covid-19 period. This type of research is descriptive quantitative research, namely by interpreting the data obtained from the field. Data collection was carried out on 4 principals and 49 teachers using a questionnaire distributed via google forms. Data analysis used descriptive quantitative with percentages. The results showed that the principal's role as a manager in online learning was not optimal in the indicators of the school determining the curriculum used in online learning (44%) and the principal facilitating support for online learning (50%), while the pedagogic competence also showed less than optimal in Playing their competencies is shown by the 5 lowest percentage indicators, including understanding the cognitive development of students (59%), designing learning methods (52%), designing learning models (56%), carrying out assessments of learning outcomes (54.5%), and conducting material assessments. (56%).